Audiovisual Media and Indonesian Language Learning Outcomes in an Islamic Elementary School - Hanna Wahyu Aruming Tyas; Muhammad Fuad; Mulyanto Widodo; Destiani (JF Publisher, 2025)
This study examined the effect of audiovisual media on the Indonesian language learning outcomes of fourth-grade students at an Islamic integrated elementary school in Metro, Lampung, focusing on the listening-and-viewing competency under the Merdeka Curriculum. Low mastery of Indonesian language material had been observed among fourth-grade students, with most of the fifty students failing to reach the school's minimum mastery criterion. A quantitative approach was applied using a quasi-experimental method with a nonequivalent control group design. The fifty students were divided into an experimental class taught with audiovisual media and a control class taught conventionally, using a saturated sampling technique. Data were collected through a fifteen-item multiple-choice pretest and posttest and analyzed using chi-square normality testing, F-test homogeneity testing, and simple linear regression. The data met the assumptions of normality and homogeneity for both administrations. The regression analysis produced the equation Ŷ = 58.66 + 0.333X with a significance value of 0.005, below the alpha level of 0.05, leading to rejection of the null hypothesis. The experimental group's mean score increased by 18.40 points, from 56.64 to 75.04, compared with a gain of only 5.22 points in the control group, despite starting from a lower baseline. These findings indicate that audiovisual media significantly improved Indonesian language learning outcomes, although the size of the effect appeared to depend on factors such as student attendance and teachers' readiness to use the medium.